Irish forestry and the Land Purchase Acts - Stanuell, Charles A. (Statistical and Social Inquiry Society of Ireland, 1912)
It is by no means a modern discovery that the presence or absence of timber seriously affects the temperature and climate of a country. It was well known before the Christian Era, and even in the Dark and Middle ages, which followed the irruption of the wild nations into what had been the Roman Empire, wrhen art and science appeared to be extinct, this knowledge seems to have survived.
Read May 10th, 1907
Keywords: Deforestation; Climate change; Forestry, Ireland; Land Purchase Acts; 314.15